Analisis Penerapan Metode Just in Time (JIT) Sebagai Alternatif Pengendalian Persediaan Bahan Baku di PT. CKA - Fajriatni, Sabine Dwiyana Puteri; Winarsih, Neneng; S, Ade Momon (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Raw material inventory control is a very crucial activity because it is done repeatedly. PT. CKA engaged in the fabrication or manufacturing of components for motorcycle and car engines and has not implemented any system or method that can help the process of controlling its raw material inventory. Therefore, in this study, calculations will be carried out regarding raw material inventory control using the Just in Time (JIT) method which aims to determine whether the process of controlling raw material inventory from the most frequently ordered products to PT. CKA, namely SPCC Plate for KYEA Arm Rear Brake products and SPHC-PO Plate for KWBF Arm Rear Brake products at PT. CKA has been effective and efficient so that it can minimize waste in the procurement process of raw materials that can affect the total cost of the raw material inventory. The results of this study show that the total cost of raw material inventory when the Just in Time method is applied has decreased by Rp10.868.938,9 from Rp11.520.165 to Rp651.226,13 with an efficiency percentage of 94% for the total cost of SPCC Plate material inventory. Meanwhile, the total cost of SPHC-PO Plate material inventory also decreased by Rp10.717.408 from Rp11.520.132,5 to Rp802.724,49 with an efficiency percentage of 93%. Keywords: Efficiency; Inventory Control; Inventory Cost; Just in Time; Raw Materials